2010
DOI: 10.22500/sodality.v4i1.5849
|View full text |Cite
|
Sign up to set email alerts
|

Reforma Agraria Dan Revitalisasi Pertanian Di Indonesia: Studi Kasus Pertanian Tanaman Pangan dan Hortikultura di Jawa Barat

Abstract: Pemanfaatan sumber-sumber agraria diharapakan dapat bermanfaat untuk kesejahteraan rakyat. Oleh karena itu, salah satu agenda yang menyangkut kebijakan agraria agar benar-benar menjadi sumber kesejahteraan adalah reforma agraria (RA). Justifikasi penelitian ini berdasarkan pada: (1) Reforma agraria merupakan program pemerintahan Susilo Bambang Yudoyono-Jusuf Kalla (2004-2009); (2) Implementasi program reforma agraria merupakan tantangan Badan Pertanahan Nasional dan stakeholders lainnya; (3) Dalam Impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…In terms of the phenomenon of disruptive innovation, the agricultural world is still dominated by the government or private entrepreneurs (incumbent). Farmers are still divided into six socioeconomic According to Sihaloho et al (2010), from the standpoint of agrarian politics, farmer poverty is generally caused by limited land tenure and a lack of productive land tenure capabilities. Agrarian reform is one component of the solution that can be implemented to provide farmers with access to agrarian/land resources (especially the poor).…”
Section: Food Sovereignty and Disruptive Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the phenomenon of disruptive innovation, the agricultural world is still dominated by the government or private entrepreneurs (incumbent). Farmers are still divided into six socioeconomic According to Sihaloho et al (2010), from the standpoint of agrarian politics, farmer poverty is generally caused by limited land tenure and a lack of productive land tenure capabilities. Agrarian reform is one component of the solution that can be implemented to provide farmers with access to agrarian/land resources (especially the poor).…”
Section: Food Sovereignty and Disruptive Innovationmentioning
confidence: 99%
“…Agrarian reform is one component of the solution that can be implemented to provide farmers with access to agrarian/land resources (especially the poor). Meanwhile, agricultural revitalization can serve as a mechanism for farmers to gain access to capital, technology, and other agricultural resources (Sihaloho et al, 2010:). In this case, Indonesia's agricultural regulatory system is still unable to attract new players into the liberal agricultural political system.…”
Section: Food Sovereignty and Disruptive Innovationmentioning
confidence: 99%
“…Secara umum pola lahan milik sendiri dan sewa cenderung sama di berbagai wilayah di Indonesia, tetapi perbedaan yang cukup signifikan terjadi pada pola pengelolaan lahan bagi hasil. Pola lahan bagi hasil memiliki nama dan aturan tersendiri pada berbagai wilayah, seperti maro di Jawa Tengah (Wahyuningsih, 2010); maro, mertelu, mrapat, dan kedokan di Jawa Timur (Malik, Wahyuni, & Widodo, 2018); nengah atau jejuron dan ceblokan di Jawa Barat (Sihaloho, Purwandari, & Mardiyaningsih, 2010); memperduai di Sumatera Barat, toyo di Minahasa, serta teseng di Sulawesi Selatan (Darwis, 2016). Perbedaan aturan masing-masing sistem bagi hasil berhubungan dengan proporsi bagi hasil dan juga kewajiban dan hak dari petani pemilik dan petani penggarap.…”
Section: Pendahuluanunclassified
“…This study describes the importance of implementing Agrarian Reform in the context of the welfare of farmers because changes in the Agrarian structure which are the basis of Agrarian Reform thinking affect and eliminate the inequality. In addition, in his other studies, Sihaloho et al (2010) explained that Agrarian Reform is one of the agendas related to Agrarian policies which are truly a source of people's welfare. Agrarian reform is considered necessary to be carried out again so that agricultural revitalization can be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Agrarian reform is considered necessary to be carried out again so that agricultural revitalization can be carried out. Sihaloho et al (2010) also revealed the reasons for the importance of implementing Agrarian Reform to overcome social and economic inequalities that occurred in West Java. Other than that, there is some other literature that discusses Agrarian Reform, Rumboko et al (2013) in their study also discusses Agrarian Reform which is an urgent need that must be done because the ownership system is a factor that greatly determines the direction of development, and the driving actor for Agrarian Reform must be pioneered by workers and farmers (Rumboko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%